2017
DOI: 10.1371/journal.pone.0189797
|View full text |Cite
|
Sign up to set email alerts
|

Limited detection of small (≤ 10 mm) colorectal liver metastasis at preoperative CT in patients undergoing liver resection

Abstract: ObjectiveTo retrospectively determine the sensitivity of preoperative CT in the detection of small (≤ 10 mm) colorectal liver metastasis (CRLM) nodules in patients undergoing liver resection.MethodsThe institutional review board approved the study and waived informed consent. We included 461 pathologically confirmed CRLM nodules in 211 patients (including 71 women; mean age, 66.4 years) who underwent 229 liver resections following abdominal CT. Prior to 163 resections, gadoxetic acid-enhanced liver MR imaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…For both open and laparoscopic surgery, the surgeons mobilized and evaluated the liver by inspection and/or palpation. In addition the surgeons or radiologists who had full knowledge of the preoperative imaging findings performed intraoperative liver ultrasonography (SSD-3500, Aloka, Japan; MylLab 25 Gold, Esaote Biomedica, Italy; or iU22, Philips Medical Systems, The Netherlands) to detect new lesions and further characterization of small indeterminate nodules 13 . Any metastatic nodules identified on intraoperative liver ultrasound (IOUS) were either resected or ablated.…”
Section: Methodsmentioning
confidence: 99%
“…For both open and laparoscopic surgery, the surgeons mobilized and evaluated the liver by inspection and/or palpation. In addition the surgeons or radiologists who had full knowledge of the preoperative imaging findings performed intraoperative liver ultrasonography (SSD-3500, Aloka, Japan; MylLab 25 Gold, Esaote Biomedica, Italy; or iU22, Philips Medical Systems, The Netherlands) to detect new lesions and further characterization of small indeterminate nodules 13 . Any metastatic nodules identified on intraoperative liver ultrasound (IOUS) were either resected or ablated.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it is crucial to ensure the best imaging method to detect them, mainly the smaller ones, which can be easily missed. Ko et al [ 50 ] showed that the sensitivity of CT was 8%, 55%, 91%, and 100% for nodules of 1-5 mm, 6-10 mm, 11-15 mm, and > 20 mm, respectively. Consequently, it appears obvious that in metastases that are "too small to characterize," CT has a limited role, particularly for those smaller than 5 mm[ 50 ].…”
Section: Deciding Between Techniquesmentioning
confidence: 99%
“…Further studies are required to establish the role of alternative imaging modalities, for example, gadoxetic acid-enhanced MRI in improving sensitivity in the detection of subcenter meter hepatic metastases particularly in patients with suspected colorectal liver metastases. 40…”
Section: Computed Tomographymentioning
confidence: 99%